Pembangunan Pendidikan Karakter Berbasis Multikultural di Pondok PesantrenBahrul Ulum Tambakberas Jombang - Huda, Saihul Atho' A'laul; Suponco, Suponco (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of the study was to determine the values of the application and learning model of character education in the Bahrul Ulum boarding school in Jombang Rice ponds. Empirically, Islamic boarding schools have a very strong culture to implement character education, both through formal and non-formal education. Character education through formal education by inculcating discipline, politeness,obedience to the rules, respect for caregivers, kiai, clerics, learning to seek knowledge, and simplicity.While character education through non-formal education includes discipline in congregational prayers,tahajjud prayers, respect for caregivers, kiai, ustadz, senior students, administrators, respect and respect for everyone. With this character education model, all students' activities are very dense and always oriented to good activities and oriented to religious activities, thus preventing students from doing negative things, both thoughts, speech, and actions. Character education has been implemented in Islamic boarding schools for a long time through habits in everyday life in the pesantren environment and through various examples or uswatun repertoires by caregivers, coaches, kyai, ustad, both in the form of behavior, ethics, morals, and speech in everyday life. -days in the boarding school environment as well as in the formal school environment. Character education in Islamic boarding schools can be used as a preventive medium to do negative things for students, both in the form of words, thoughts, and actions. The results of this study can contribute to the development of character education-based education that can be applied in formal and non-formal education, both in public and private schools.